Tubo que morir Jesucristo para que se pintaran los tambores en Hellín / Jesus Christ had to die for the drums to be painted in Hellín - Fernando Picornell Cantero (Anastasis: Research in Medieval Culture and Art, 2020)
Fernando Picornell's artwork painted on drums of Hellin region from Spain. Based on knowledge acquired from studying of drums from Hellin region since the very beginning to nowadays in its different ways of representations, the artist developed this subject within an artwork which is also a reason for meditation upon visual arts and painting.